The Compounds Containing Imidazol-5-one Heterocycle: Synthesis and Biological Activities - Nguyen, Cong Tien (New Innovations in Chemistry and Biochemistry Vol. 7, 2022)
In recent years, heterocyclic compounds have become more and more important and they have been receiving special attention from chemists because of their pharmacological activities. Imidazole is a five-membered heterocycle with nitrogen atoms in 1 and 3 positions. Being a derivative of imidazole, imidazol-5-one nucleus has also been of interest to research and this heterocycle has been present in the composition of many compounds with biological activities. This work aims to review the reported research on the synthesis and pharmacological activities of imidazol-5-one derivatives during past years. Accordingly, the imidazol-5-one ring is usually formed from an oxazol-5-one ring or from cyclization of the 3-aryl-2-alkanoylamidoacrylohydrazides. In addition, the reported major biological activities of compounds containing imidazol-5-one heterocycle include antimicrobial activity (antibacterial, antifungal), anti-inflammatory activity, analgesic activity, cytotoxic activity, anthelmintic activity and antioxidant activity.